Implementing Secondary Publication Right in Copyright Law for Green Open Access to Research - Majekolagbe, Faith (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2026)
This article argues that, as the Canadian government and governments in peer jurisdictions adopt open access policies requiring researchers to provide free and immediate (embargo-free) public access to research publications resulting from government-funded research projects, the green road to open access (self-archiving) must remain a viable means of complying with these policies. This is essential to ensure that government open access policies do not create an unsustainable dependency on limited government resources. Although the gold road to open access offers immediate access, it often necessitates the payment of article processing fees demanded by publishers. In contrast, the green road to open access does not require payment to publishers for public access to a reliable version of the research publication (the author’s accepted manuscript); however, researchers frequently have limited authority to provide open access to their works in this manner when publishers acquire their copyrights and impose restrictions on republication. Such restrictions typically take the form of embargoes on republication, which undermine opportunities to use the green road to deliver immediate public access to research. Researchers often have weak, and sometimes nonexistent, bargaining power. Consequently, it is frequently challenging for them to navigate the publishing industry’s contractual framework that secures copyrights for free, prevents researchers from retaining the rights necessary to republish their accepted manuscripts on an open access basis, and limits their capacity to provide immediate public access to research by imposing embargoes on republication. To support the green road to open access as a viable option for researchers to provide immediate public access to research, I argue that Canada and other countries must implement, alongside their open access policies, a legislative strategy involving a secondary publication right within copyright law. This article proposes an ideal secondary publication right framework and advocates for its implementation in Canada and beyond.